18F-fludeoxyglucose positron emission tomography for diagnosis of HCC: implications for therapeutic strategy in curative and non-curative approaches. (March 2019) - Kornberg, Arno; Friess, Helmut
Hepatocellular carcinoma (HCC) is a global health issue with increasing incidence and high mortality rate. Depending on the tumor load and extent of underlying liver cirrhosis, aggressive surgical treatment by hepatectomy or liver transplantation (LT) may lead to cure, whereas different modalities of liver-directed locoregional or systemic tumor treatments are currently available for a noncurative approach. Apart from tumor burden and grade of liver dysfunction, assessment of prognostic relevant biological tumor aggressiveness is vitally important for establishing a promising multimodal therapeutic strategy and improving the individual treatment-related risk/benefit ratio. In recent years, an increasing body of clinical evidence has been presented that 18 F-fludeoxyglucose ( 18 F-FDG) positron emission tomography (PET), which is a standard nuclear imaging device in oncology, may serve as a powerful surrogate for tumor invasiveness and prognosis in HCC patients and, thereby, impact individual decision making on most appropriate therapy concept. This review describes the currently available data on the prognostic value of 18 F-FDG PET in patients with early and advanced HCC stages and the resulting implications for treatment strategy.